AB0815 Health related quality of life in patients with systemic sclerosis treated with two different intravenous iloprost regimens. (12th June 2018) - Schioppo, T.; Scalone, L.; Cozzolino, P.; Mantovani, L.; Cesana, G.; De Lucia, O.; Murgo, A.; Ingegnoli, F.
Abstract : Background: In systemic sclerosis (SSc), Raynaud's phenomenon (RP) and digital ulcers (DU) can decrease health related quality of life (HRQoL). Intravenous (IV) iloprost (ILO) is administered for RP, after oral therapy failure, and DU healing. HRQoL is considered fundamental to assess the impact of the disease and therapy on patients: EQ-5D-5L has been satisfactory used to assess the general HRQoL in SSc. Objectives: Aim of our study was to estimate HRQoL in SSc patients treated with two different IV ILO regimens and in patients not requiring IV ILO. Methods: This was a monocentric, prospective, pragmatic and non-randomised study. Enrolled SSc patients were divided into 3 groups: no IV ILO (group A), IV ILO once monthly (B) or IV ILO for 5 consecutive days every 3 months (C). HRQoL was assessed using EQ-5D-5L through a telephone interview. Group A patients were evaluated at baseline and after 3 months; group B 2 days before each infusion and 2 weeks after each infusion; group C 2 days before each therapy cycle, and after 2 and 6 weeks after the first cycle of therapy. The EQ-5D-5L describes HRQoL, measures the overall health state with a 0–100 visual analogue scale (VAS) and values health with a utility index. Multiple regression analyses was performed to calculate VAS and mean utility index in each group (confounders: age, sex, treatment group, baseline utility or VAS score, average outdoor temperature the week before the evaluation at patient's place of residence, RP VAS, disease duration and modified Rodnan skin score). Results: 96 patients were enrolled: 52 in group A, 24 in B, and 20 in C. Of these 35, 21 and 16 completed the study respectively. Utility and VAS score at the end of the three months, as adjusted for the possible confounders, were not statistically different in the three groups. Conclusions: Utility and VAS, at 3 months follow-up, were not different in the 3 groups as if IV ILO was able to make patients requiring IV ILO as similar as patients not requiring IV ILO. Moreover, in this model there was no difference between the two ILO regimens (1 days monthly vs 5 every 3 months). These results suggest that our therapeutic approach, based on various criteria such as demographic, clinical characteristics, logistic aspects and patients' preferences, allows to reach or to maintain HRQoL at comparable levels between the three groups considered. Acknowledgements: Meteo Operations Italia SrL – Centro Epson Meteo for temperature data. Disclosure of Interest: None declared